Economy-wide impacts of technological change in the agro-food production and processing sectors in Sub-Saharan Africa - Ehui, Simeon; Delgado, Christopher L. (International Food Policy Research Institute, 1999)
Processing of meat and crops accounts for a large share of manufacturing in Sub-Saharan Africa (SSA). The paper assesses empirically the impact of hypothesized productivity change in agro-food processing on growth, trade, employment, and input and output prices in SSA, using a 13 commodity, 7 region version of the Global Trade Analysis Project (GTAP) applied general equilibrium model with a 1995 database. Results are compared to impacts of factor-neutral and biased technical change in primary agricultural production -- grains, non-grain crops, and livestock -- overall and with respect to the agro-food sector itself. A given percentage increase in total factor productivity in primary agricultural production is shown by every criterion to have much greater favorable impacts than the same increase in any form of technical change in processing, even when consideration is given only to the welfare of people in the agro-food processing sector itself. Technological change in the non-grain high value agricultural sectors such as horticulture and livestock are second-best, but still powerful promoters of increased welfare. However, the paper is not able to assess the costs or likelihood of securing different kinds of technical change, and therefore comparisons are limited to the benefit side.